2018
DOI: 10.1016/j.nmni.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic characterization of Staphylococcus aureus isolated from a burn centre by using agr, spa and SCCmec typing methods

Abstract: Infections caused by Staphylococcus aureus remain a major global healthcare problem. We aimed to find the common lineages of S. aureus strains circulating in a burn hospital in Tehran. A total of 167 isolates of S. aureus obtained from patients, healthcare workers (HCWs) and environment in Shahid Motahari burn hospital were genotyped by using spa, agr and staphylococcal cassette chromosome mec (SCCmec) typing methods. Antimicrobial susceptibility testing was performed by using the disc diffusion method. The fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 28 publications
7
20
0
Order By: Relevance
“…All of the MRSA isolates in the present study were MDR which is in relative line with previous reports from Iran [2,14] and Taiwan [38]. Our ndings also suggested that vancomycin and linezolid are potent and effective treatment options for MRSA [35,40,41].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All of the MRSA isolates in the present study were MDR which is in relative line with previous reports from Iran [2,14] and Taiwan [38]. Our ndings also suggested that vancomycin and linezolid are potent and effective treatment options for MRSA [35,40,41].…”
Section: Discussionsupporting
confidence: 92%
“…The relative prevalence (38.14%) of HA-MRSA strains in our study was comparable to the result obtained by Darban et al (35%) [35]. However, this prevalence was lower than that reported in America, Europe, Africa, and Asia [26,[36][37][38][39][40][41]. The reasons for this discrepancy in the prevalence of MRSA may be related to the dissimilar antibiotic usage patterns, contrary infection control policies, sources of the isolates, and the characteristics of the subjects (HCWs and patients).…”
Section: Discussionsupporting
confidence: 86%
“…The acquisition and diversity of different SCCmecs are crucial [52], and it is through that methicillinsusceptible S. aureus (MSSA) becomes MRSA. SCCmec carries either the mecA or mecC gene, regulatory genes, ccrAB or/and ccrC site-specific recombinase genes, and a variety of accessory genes encoding for a new specific penicillin-binding protein (PBP2a) [53,54]. The SCCmec element contains three J regions, besides the mec and ccr gene complexes, they were first report as the L-C, C-M, and I-R regions but were later changed to J regions.…”
Section: Resistance Mechanismmentioning
confidence: 99%
“…For both MRSA and MRCoNS vancomycin is used as the first line drug for treatment. However, in recent years, decreased susceptibility and even resistance to vancomycin and other antibiotics, including aminoglycosides, tetracyclines, and lincosamides, have been reported in many parts of the world [5][6][7]. Therefore, for the treatment of severe infections caused by multi-drug resistant staphylococci, new antibiotics such as daptomycin, linezolid, tigecycline, and Quinupristin/Dalfopristin (Q/D) were introduced [8].…”
Section: Introductionmentioning
confidence: 99%